Antibacterial And Antifungal Activity Of Some Medicinally Important Plants - BABEET SINGH TANWER; SATYAPAL SINGH; REKHA VIJAYVERGIA (International Journal of Pharma and Bio Sciences, 2012)
The ethanolic extracts of different plant parts of Alangium salviifolium Linn, Andrographis paniculata Nees and Spilanthus acemella Murr showed significant antibacterial activity against Escherichia coli, Pseudomonas aureginosa, Staphylococcus aureus and antifungal activity against Aspergillus flavus A. niger, A. fumigatus and Fusarium oxysporium. Alangium salviifolium root extract and S. acemella leaf extract showed highest antibacterial activity against E. coli and Staphylococcus aureus. Root and stem extracts of Alangium salviifoilium recorded significant activity against all the test bacteria and fungi.